Market reactions to supervisory signs on Stock Exchange of Thailand. - Koh, Andy Leng Huat. (2008)
This paper investigates the impact of trading signs posted by the Stock Exchange of Thailand (SET) on return, volatility and trading volume of stocks assigned the NP (Notice Pending) and SP (Trading Suspension) supervisory signs.